Evaluasi Penggunaan Obat pada Pasien Balita Terkena Diare pada Pasien Rawat Inap RSUD Kota Surakarta Tahun 2014 - Septiani, Sundari, Zakky Cholisoh, M.Clin.Pharm., Ph.D., Apt (2016)
Diarrhea is a disease which marked by increasing frequency of defecation more than three times in a day that accompanied by liquid stools with or without blood or mucus. According to Word Gastroenterology organisation (2012), management of children with acute diarrhea consist of oral rehidration, zinksuplements therapy, diet, probiotics, and antibiotics. The purpose of this research is to evaluate the rational use of antibiotics, antidiarrhearesion, and probiotics prescribing in children (0-5 year old) with diarrhea inpatient of X hospital. The research is a-non experimental research. Datarestropectively was obtained from medical record. Data was descriptively analyzedsixty nine patients were included as sample by purposive sampling method. Results of the evaluation of antibiotic use in X hospital were given with right indication 46.38%, with the right patients 100%, with the right drug 100%, and the right dose 4.35%. Results of the evaluation of Zink with the right indication, patients, drug were 94.20%, and the right dose were given to 53 patients 76,81%. Results of the evaluation of probiotics with the rightindication, patients, drug were89.68%, and the right dose were 14.50%.